Economic base of buildings purchase contract/Statybos viešųjų pirkimų kontraktų ekonominis pagrindimas - Bagdonas, Vilhelmas (Journal of Civil Engineering and Management, 2001)
In the article, the organisation of procedures of public purchases and the economical effectiveness of purchase as well as economical substantiation are investigated. Public purchases in Lithuania are compared with the EU and with world countries experience and provide principles of their harmonisation. Public purchases organised in a proper way allow to save from 5% up to 50% of taxpayers' means. Public purchases are organised in all the EU countries, that's why it is necessary to manage and to compare their procedures in order to harmonise principles. In the article, the order of public purchases, economic substantiation according to concrete competition data are analysed. It is suggested to evaluate the results as a complex, that is not only by the lowest price, but also by functional qualities of the building, operational expenditures, service capacity of the object, aesthetic and ecologic qualities and the specific methods are suggested for the evaluation of qualities mentioned.Article in Lithuanian.First Published Online: 30 Jul 2012